Magnetron sputtering of Si-Al-N nanocomposite coatings on quartz for protection against impacts of high speed microparticles; Vacuum; Vol. 143 - Sergeev V. P. Viktor Petrovich; Psakhie S. G. Sergey Grigorievich; Chubik P. S. Peter Savelievich; Chernyavsky A. G. Aleksandr Grigorjevich; Solovjev V. A. Vladimir Alekseevich; Solntsev V. L. Vladimir Lvovich; Khristenko Yu. F. Yury Fedorovich (2017, 2017)
Title screen